Alcohol use among young Australian adults in May–June 2020 during the COVID‐19 pandemic: a prospective cohort study. (24th June 2021) - Clare, Philip J.; Aiken, Alexandra; Yuen, Wing See; Upton, Emily; Kypri, Kypros; Degenhardt, Louisa; Bruno, Raimondo; McCambridge, Jim; McBride, Nyanda; Hutchinson, Delyse; Slade, Tim; Mattick, Richard; et al.
Abstract: Aims: To estimate change in young people's alcohol consumption during COVID‐19 restrictions in Australia in early‐mid 2020, and test whether those changes were consistent by gender and level of consumption prior to the pandemic. Design: Prospective longitudinal cohort. Setting: Secondary schools in New South Wales, Tasmania and Western Australia. Participants: Subsample of a cohort ( n = 443) recruited in the first year of secondary school in 2010–11. Analysis data included three waves collected in September 2017–July 2018, September 2018–May 2019 and August 2019–January 2020), and in May–June 2020. Measurements: The primary predictors were time, gender and level of consumption prior to the pandemic. Outcome variables, analysed by mixed‐effects models, included frequency and typical quantity of alcohol consumption, binge drinking, peak consumption, alcohol‐related harm and drinking contexts. Findings: Overall consumption (frequency × quantity) during the restrictions declined by 17% [incidence rate ratio (IRR) = 0.83; 95% confidence interval (CI) = 0.73, 0.95] compared to February 2020, and there was a 35% decline in the rate of alcohol‐related harms in the same period (IRR = 0.66; 95% CI = 0.54, 0.79). Changes in alcohol consumption were largely consistent by gender. Conclusions: From a survey of secondary school students in Australia, there is evidence for a reduction in overall consumption and related harms during the COVID‐19 restrictions.